The Effect of Learning Models on Volleyball Passing Learning Outcomes, as Seen in The Senior High School of Self-Efficacy in Students of State Junior High School 3 Amlapura - Komang Ayu Laksmi Saputri; I Ketut Yoda; I Ketut Iwan Swadesi (Journal of Physical Education Health and Sport, 2025)
The mastery of volleyball overhead passing is a fundamental yet complex skill for junior high school students, often hindered by traditional teaching methods and students’ lack of self-confidence. This study aims to evaluate the effectiveness of the Project-Based Learning (PjBL) model compared to Direct Instruction on volleyball passing outcomes, while specifically analyzing the role of students’ self-efficacy levels. The study utilized a quantitative experimental approach with a 2 × 2 factorial design. To categorize student performance, five predefined score thresholds were applied: Very Good (>75), Good (58–75), Fair (42–57), Poor (25–41), and Very Poor (<25). The sample consisted of eighth-grade students at State Junior High School 3 Amlapura. Data were collected through self-efficacy questionnaires and standardized volleyball passing tests, subsequently analyzed using two-way ANOVA at a significance level of 0.05. The findings indicate that students taught through PjBL achieved significantly higher scores than those under Direct Instruction. Furthermore, students with high self-efficacy consistently outperformed those with low self-efficacy. A significant interaction effect (p < 0.05) was found between the learning model and self-efficacy; the combination of PjBL and high self-efficacy yielded the highest outcomes in the “Very Good” category, whereas Direct Instruction with low self-efficacy resulted in the lowest “Poor” performance. It is concluded that PjBL is a superior instructional model for enhancing volleyball skills, provided that students’ psychological readiness and self-efficacy are also prioritized in the learning process.